Exploring the influence of principal supervision, organizational climate, and teacher teaching experience on teacher performance - Kasih, Estu Widiyana; Sohnui, Suhailee; Mundilarno, Mundilarno (Indonesian Journal of Educational Management and Leadership, 2024)
Purpose− The purpose of the research is to examine the combined and individual effects of school principals' supervision, organizational climate, and teacher teaching experience on teacher performance in Sub Rayon 03 Middle School in Purworejo Regency. The research method used was quantitative, and the analysis employed multiple linear regression analysis Method− The research employs a quantitative correlational approach, conducted at SMP Sub Rayon 03 Purworejo Regency with a sample of 95 teachers selected from a population of 130 using Isaac and Michael's sampling table. Data collection was carried out using research instruments, and the analysis involved multiple linear regression and partial correlation. Multiple linear regression was used to assess the combined effect of principal supervision, organizational climate, and teaching experience on teacher performance. Partial correlation analysis was conducted to determine the individual contributions of each variable to teacher performance. The significance of the regression equation was tested using the F test, while the t test was used for testing partial correlations. Findings− The analysis results concluded the following: 1) There was a positive and significant combined influence of principal supervision, organizational climate, and teacher experience on teacher performance in Middle Sub-Rayon 03, Purworejo District (R=0.635 and R2=0.403). 2) Principal supervision had a positive and significant impact on teacher performance in Sub-Rayon 03 Middle School District, Purworejo (r1y-23=0.251). 3) Organizational climate also had a positive and significant effect on teacher performance in Sub-Rayon 03 Middle School, Purworejo District (r2y-23=0.319). 4) Finally, teacher teaching experience contributed positively and significantly to teacher performance in Sub-Rayon 03 Middle School, Purworejo District (r3y-12=0.260).